ANTONYMIC PECULIARITIES OF BLESSING AND CURSE PHRASES IN ENGLISH AND UZBEK LANGUAGES - Norkobilova Nigora Uralovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. Blessing and curse phrases represent two opposite poles of expressive language, functioning as linguistically and culturally marked speech acts. This article investigates the antonymic peculiarities of blessing and curse phrases in English and Uzbek, focusing on semantic opposition, structural contrast, and pragmatic realization. The study identifies major antonymic pairs, analyzes their semantic fields and expressive intensity, and reveals both universal and language-specific features. The findings demonstrate that antonymy between blessing and curse phrases reflects not only lexical opposition but also deep-rooted cultural values and worldviews.